Myth, fantasy and fairy-story in Tolkien’s Middle-Earth / Buveneswary Vathemurthy - Buveneswary, Vathemurthy (2017)
This dissertation explores J.R.R. Tolkien’s ideas and beliefs on myth, fantasy and fairy story and their roles in portraying good and evil in his famous works. Indeed, many authors and critics such as Bradley J. Birzer, Patrick Curry, Joseph Pearce, Ursula Le Guin, and Jay Richards have researched Tolkien based on this connection. They have worked on the nature of good and evil in his stories, the relevance of Tolkien in contemporary society, and the importance of myth and fantasy. However, my original contribution would be to examine the pivotal roles of myth, fantasy and fairy story as a combined whole and to demonstrate that they depend on one another to convey truths about good and evil. This research is aimed at showing that Middle-earth evolves from a combination of these three genres. This is made evident by the way Tolkien crafted his lecture On Fairy Stories for a presentation at the Andrew Lang lecture at the University of St Andrews in 1939. This dissertation then examines Tolkien’s own definitions of myth, fantasy and fairy stories and his extensive research on these “old-fashioned” or forgotten genres. He believed they could provide a cure for the moral and human degradation triggered by modernism. This study also investigates various criticisms, biographical books written by Tolkien experts, Tolkien’s personal letters, various philosophical and academic essays and mainly his works to unravel the questions that need answering. My discussion aims to show that the combination of these genres and their methods of representation, ultimately deliver a message of goodness, faith and a respect for tradition. Finally, this thesis finds that Tolkien’s noble aims and ambitions behind his legendarium are tied to an enduring faith in God and in moral and social responsibility.